Inorganic chemistry - Shriver, D.F.; Atkins,P.W; Langford,C.H; etc.; Atkins, P.W.; Langford, C.H. ([S.l.] : Oxford University Press, 1990)
The student of inorganic chemistry must master the chemistry of the elements. This presentation of the subject provides factual information and important principles within the context of broad chemical concepts and periodic trends.
Keywords: Chemistry